Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1093/ajh/hpv063
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Reducing Sedentary Time With Vascular Function and Insulin Sensitivity in Older Sedentary Adults

Abstract: Reductions of up to 100 minutes of sedentary time per day over 12 weeks was not significantly associated with improved vascular endothelial function in older adults. FMD% was significantly higher among those with lower sedentary behavior and concomitant moderate-intensity PA of ≥20 minutes/day in bouts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…LightEE was a significant predictor of weight and FM loss, which suggests that even lightPA may play a role during the early phase of weight loss in these patients. The strong associations with sedentary time and SedEE support previous studies reporting sedentary behavior as an independent risk factor for health ( 37 , 38 , 39 ), even after accounting for the influence of RMR reduction. Finally, the model including the PA variables revealed that LightPA was a significant predictor of weight and FM loss, which is supported by our quartile dose-response analysis.…”
Section: Discussionsupporting
confidence: 86%
“…LightEE was a significant predictor of weight and FM loss, which suggests that even lightPA may play a role during the early phase of weight loss in these patients. The strong associations with sedentary time and SedEE support previous studies reporting sedentary behavior as an independent risk factor for health ( 37 , 38 , 39 ), even after accounting for the influence of RMR reduction. Finally, the model including the PA variables revealed that LightPA was a significant predictor of weight and FM loss, which is supported by our quartile dose-response analysis.…”
Section: Discussionsupporting
confidence: 86%
“…Reyes et al also found a higher FMD response in active versus inactive pregnant women, defined by time in MVPA 57. Suboc et al found a similar correlation in participants with ≥20 min/day of MPA in bouts, which was not statistically significant, perhaps due to underpowering of the study ( n =96) 46. Suboc et al also found that MPA in bouts, rather than overall time in MPA, was associated with change in FMD 47.…”
Section: Resultsmentioning
confidence: 95%
“…In contrast, Gando et al suggested no relationship between arterial stiffness with VPA, while there was an inverse relationship for MPA and LPA in older subjects 43. Several studies found no relationship between higher intensity PA with arterial stiffness 23 44–49. Some studies investigated specific patient populations, with differing results for subsets of patients 50 51.…”
Section: Resultsmentioning
confidence: 98%
“…An increase of DBP more than 10 mmHg above the resting value or an absolute value of 90 mmHg also is considered abnormal and could predict increased likelihood of CAD. EST termination should be made when SBP is more than 250 mmHg and DBP more than 115 mmHg, respectively [202,[206][207][208]. A resting SBP >200 mmHg and DBP >110 mmHg are considered relative contraindications to EST.…”
Section: Blood Pressure (Bp) Abnormalitiesmentioning
confidence: 99%